Examining the effect of child labour in the profitability of women owned enterprises: A case of microcredit supported enterprises in Tanzania - Charles S. Tundui; Hawa P. Tundui (Journal of Global Entrepreneurship Research, 2018)
This paper examines the effect of child labour in the profitability of women owned enterprises. The study covered 429 women respondents who had access to microcredit in Morogoro and Iringa towns. We used the Ordered Probit to model the relationship between the predictors and the outcome variable. The findings show that the use of child labour plays a more significant role in the profitability of women businesses than any variable included in the analysis. Results have also shown that owners who possess business skills, who have access to markets and those who do not separate business resources from household resources are more likely to experience a profit increase in their enterprises than otherwise. On the other hand, access to loans doesn't seem to translate into increases in enterprise profit. From these results, we gather that as a poverty alleviation strategy, microcredit access and micro enterprising are not a panacea, but will require other supporting policies and services to enable women to find their way out of poverty. It is also important that job creation and employment patterns of microcredit supported enterprises are studied and valued accordingly.
Keywords: 650; Child labour; Profitability; Women-owned enterprises; Microcredit supported